2021
DOI: 10.1038/s41380-020-00985-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of gene dosage in 24,092 individuals estimates that 10,000 genes modulate cognitive ability

Abstract: Genome wide analysis of gene dosage in 24,092 individuals estimates that 10,000 genes modulate cognitive ability Single sentence summary: CNVs' effect-sizes on intelligence are predicted using measures of intolerance to haploinsufficiency and are distributed across half of the coding genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

7
2

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 42 publications
2
67
0
Order By: Relevance
“…Although sample sizes will not allow gene based association studies in the near future, "function based" genome wide association studies could be conducted by partitioning and scoring rare variants based on genes functions and pathways. Such analytical strategies have been used successfully for the investigation of CNV effects on cognition (90,91) and risk for ASD (17) but they imply some level of functional convergence (ie, CNVs encompass genes with similar functional annotation also show similar alterations at the neuroimaging level). Such an approach would provide insight into mechanisms linking microscale variation to macroscale brain network alterations.…”
Section: Perspective and Future Directionsmentioning
confidence: 99%
“…Although sample sizes will not allow gene based association studies in the near future, "function based" genome wide association studies could be conducted by partitioning and scoring rare variants based on genes functions and pathways. Such analytical strategies have been used successfully for the investigation of CNV effects on cognition (90,91) and risk for ASD (17) but they imply some level of functional convergence (ie, CNVs encompass genes with similar functional annotation also show similar alterations at the neuroimaging level). Such an approach would provide insight into mechanisms linking microscale variation to macroscale brain network alterations.…”
Section: Perspective and Future Directionsmentioning
confidence: 99%
“…Previous studies demonstrated that the effect-size of CNVs on IQ increases approximately linearly with the number of encompassed genes. The number of deleted genes (weighted by dosage sensitivity) predicts IQ with 78% accuracy ( 10, 11 ). We observed a correlation between the effect size of CNVs on FC and their previously estimated effect size on cognitive ability( 10 ) ( r =0.86, p =2.06e -05 ) and risk for either ASD( 24, 25 ) or SZ ( 26, 27 ) ( r =0.76, p =0.02).…”
Section: Resultsmentioning
confidence: 99%
“…The latter has been modeled for SNPs, using polygenic scores (PGS), which are weighted sums of genetic risk alleles ( 9 ). Similar models applied to rare variants show that the effects of CNVs on cognition are the sum of individual effects of genes encompassed in the CNV, weighted by their sensitivity to gene dosage ( 10, 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…A weighted linear model was developed to estimate the effect of CNVs on IQ using scores of intolerance to protein loss of function in a dataset of 24 000 individuals from unselected and psychiatric cohorts with cognitive assessments. 132–134 These models could predict the effect size of any CNV with 80% accuracy. Deletions of >50% of the coding genome negatively impacted IQ, and this is consistent with infinitesimal/omnigenic models.…”
Section: Bottom-up Approach: Large Effect Genetic Variants To Dissect Mechanisms In Psychiatrymentioning
confidence: 99%